PENGARUH PENERAPAN QUALITY CONTROK TERHADAP KINERJA KARYAWAN DALAM MENJAGA KUALITAS PRODUK DI PT INDONESIA EPSON INDUSTRY - Tiyani, Tiyani; Haji, Son; Wayhuni, Sri (Bussman Journal : Indonesian Journal of Business and Management, 2025)
This study aims to analyze the effect of quality control implementation on employee performance in maintaining product quality at PT Indonesia Epson Industry Cikarang, in response to the challenge of quality consistency in the manufacturing industry. Adopting a descriptive-correlational quantitative approach, this study uses a Likert scale questionnaire as a primary data collection instrument from a sample of employees in the production department. Instrument testing was conducted on 20 respondents to ensure its validity and reliability. The collected data were analyzed using classical assumption tests, simple linear regression, and the coefficient of determination. The results indicate that the implementation of quality control has a significant and positive influence on employee performance, with a coefficient of determination (R²) of 0.903. This means that 90.3% of employee performance variation is influenced by quality control, while the remainder is explained by other factors. The conclusion emphasizes that effective quality control implementation is a crucial factor in optimizing employee performance and suggests further research to examine other variables influencing performance